2001
DOI: 10.1007/s15010-001-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Genotyping versus Serotyping in Egyptian Patients

Abstract: Type 4 HCV is the most prevalent type in Egyptian CAH patients and there is a high concordance between the results of serotyping and genotyping techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 9 publications
(15 reference statements)
3
12
2
Order By: Relevance
“…Overall, this performance was consistent with those described elsewhere (2,12,15,39). The genotyping assay failed for three samples, which were later identified as type 2 by the serological method.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, this performance was consistent with those described elsewhere (2,12,15,39). The genotyping assay failed for three samples, which were later identified as type 2 by the serological method.…”
Section: Discussionsupporting
confidence: 89%
“…The sensitivity of the serological typing assay was 70% in relation to the results obtained by the genotyping assay. This rate, which is lower than those previously reported (23,37,39), could be explained by the high prevalence of genotype 5 in the population studied. Gault et al recently reported that a kit from the same manufacturer using a new version of the HCV serotyping 1-6 assay gave better results for rare types (11).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…This disagreement was reported by others [Chen and Weck, 2002;Nolte et al, 2003]. The lack of agreement reported in this study at the subtype level is not surprising considering the high diversity of genotype 4, especially in the Egyptian population as previously shown by others [Zekri et al, 2001] comparing sero-and geno-typing methods, The detection of a large number of individual mutated strains by hybridization assay such as INNO-LiPA in a single test is difficult since it requires very high stringent conditions [Ansaldi et al, 2001]. Also the lack of agreement between the subtypes is not unusual considering that both methods target the 5 0 NC region.…”
Section: Discussioncontrasting
confidence: 66%
“…Chronic hepatitis and liver cirrhosis have been documented in 70% and 20%, respectively, of those chronically infected [2,3]. Egypt has an overall HCV antibody prevalence around 15% in the general population [4][5][6][7] and genotype 4 has been identified in about 90% of HCV isolates [8][9][10][11][12]. Despite recent improvements in antiviral therapy with interferon and ribavirin, only about half of those who meet the criteria for treatment will respond to therapy.…”
Section: Introductionmentioning
confidence: 99%